The Implementation of E-Procurement within the Procurement Service Unit (UKPBJ) of the Directorate General of Corrections in Lampung - Vike Youdit; Intan Fitri Meutia; Dian Kagungan; Noverman Duadji (Journal of Engineering and Applied Technology, 2025)
This study examines the empirical implementation of e-procurement within the Procurement Service Unit (UKPBJ) of the Directorate General of Corrections in Lampung, focusing on accountability, effectiveness, and transparency outcomes. Utilizing a qualitative descriptive approach, data were collected through in-depth interviews, non-participant observation, and document analysis, while analytical validation employed triangulation and the interactive model of data reduction, display, and iterative conclusion verification. Findings indicate that digital systems such as SPSE, e-catalogue, and INAPROC have substantially improved traceability and procedural order in procurement activities, enabling more efficient supplier selection, contract management, and monitoring of procurement stages. Nevertheless, optimal outcomes are hindered by infrastructure disparities, limited human resource competencies, and inconsistent managerial support, which constrain uniform adoption and system utilization. Regulatory support and policy clarity significantly influence implementation success, while leadership and capacity-building emerge as pivotal enablers. The study contributes to e-procurement literature by empirically validating socio-technical determinants of digital procurement performance, highlighting the need for coordinated interventions in technological readiness, institutional governance, and personnel development to fully realize transparency, accountability, and efficiency objectives in public sector procurement